2011
DOI: 10.1007/s00401-011-0879-y
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 pathological changes in early onset familial and sporadic Alzheimer’s disease, late onset Alzheimer’s disease and Down’s Syndrome: association with age, hippocampal sclerosis and clinical phenotype

Abstract: TDP-43 immunoreactive (TDP-43-ir) pathological changes were investigated in the temporal cortex and hippocampus of 11 patients with autosomal dominant familial forms of Alzheimer's disease (FAD), 169 patients with sporadic AD [85 with early onset disease (EOAD) (i.e before 65 years of age), and 84 with late onset after this age (LOAD)], 50 individuals with Down's Syndrome (DS) and 5 patients with primary hippocampal sclerosis (HS). TDP-43-ir pathological changes were present, overall, in 34/180 of AD cases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
111
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 38 publications
18
111
3
Order By: Relevance
“…TDP-43 has been discovered in both sporadic and familial AD [46][47][48] , and our seeding results showed that TDP-43 oligomers can interact and influence Ab fibrillization. The increased Ab assembly in the presence of TDP-43 could result from a seeding effect that generates new Ab assemblies such as Ab*56 and larger aggregates or formation of cross-linked TDP-43 and Ab complexes.…”
Section: Discussionmentioning
confidence: 54%
“…TDP-43 has been discovered in both sporadic and familial AD [46][47][48] , and our seeding results showed that TDP-43 oligomers can interact and influence Ab fibrillization. The increased Ab assembly in the presence of TDP-43 could result from a seeding effect that generates new Ab assemblies such as Ab*56 and larger aggregates or formation of cross-linked TDP-43 and Ab complexes.…”
Section: Discussionmentioning
confidence: 54%
“…Although some studies on HS‐Aging explicitly state a sparing of CA2/3 in HS‐Aging diagnosis 16, 17, 24, 27, 31, 55, others include cases which present with neuron loss also in other hippocampal sectors than the CA1 and subiculum 15, 29, 43, 44, 57, 58. Frequently, the term “selective” is used for CA1 neuron loss and gliosis, but how potential lesions in other CA areas are considered is not further specified (for example 2, 7, 26, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, observations of AD-DS neuropathology already underpin our mechanistic Pathological features other than plaques and NFTs also develop in both AD-DS and LOAD. Neuronal accumulation of ubiquitylated and aggregated transactive response DNA-binding protein 43 (TDP43; also known as TARDBP) in the cytoplasm and neurites is similar in AD-DS (7-14% of cases) and familial AD (10-14% of cases), whereas TDP43 neuropathology occurs more frequently in LOAD (29-79% of cases), perhaps because of the later disease onset 101,102 . Lewy bodies, particularly in the amygdala, occur at a similar frequency in AD-DS and LOAD 103 , but dementia with Lewy bodies (DLB), which is characterized by cognitive decline with hallucinations and parkinsonism features, is rare in DS 104 .…”
Section: Neuropathological Changes In Ad-dsmentioning
confidence: 99%